Development of Android-based landslide disaster mitigation learning media for disabilities elementary school - Aulia Qisthi Rosyada; Dias Aziz Pramudita; Ika Candra Sayekti; Siti Azizah Susilawati (Universitas Negeri Yogyakarta, 2023)
The Klaten Regency area is included as a disaster-prone area. One of the disasters that often hit this district are landslides. This increases the risk that human safety is threatened, especially for people with disabilities. This condition will get worse if they do not have education about disaster mitigation. This study aims to develop an Android-based landslide disaster mitigation medium for elementary school disabilities. This media uses three types of software: Kodular to create Android applications, Blender to create 3D animations, construct to make games, and FlipPDF to create e-books. This study used the Research and Development (RD), research method in conjunction with a waterfall process development model. To get the feasibility results, this medium was tested on experts and users, the first being tested on two media experts, with a percentage result of 88.8%, so that it was declared very feasible. The second was tested on two e-book material experts with a percentage of 98.5%, so it was declared very feasible. The third was tested on two video material experts with a percentage of 98.94%, so it was declared very feasible. The fourth was tested on users and got a percentage result of 78.4%, so it was stated that this medium was appropriate.